Hypofractionation in Prostate Cancer: Radiobiological Basis and Clinical Appliance. (30th April 2014) - Mangoni, M.; Desideri, I.; Detti, B.; Bonomo, P.; Greto, D.; Paiar, F.; Simontacchi, G.; Meattini, I.; Scoccianti, S.; Masoni, T.; Ciabatti, C.; Turkaj, A.; et al.
Abstract : External beam radiation therapy with conventional fractionation to a total dose of 76–80 Gy represents the most adopted treatment modality for prostate cancer. Dose escalation in this setting has been demonstrated to improve biochemical control with acceptable toxicity using contemporary radiotherapy techniques. Hypofractionated radiotherapy and stereotactic body radiation therapy have gained an increasing interest in recent years and they have the potential to become the standard of care even if long-term data about their efficacy and safety are not well established. Strong radiobiological basis supports the use of high dose for fraction in prostate cancer, due to the demonstrated exceptionally low values of α / β . Clinical experiences with hypofractionated and stereotactic radiotherapy (with an adequate biologically equivalent dose) demonstrated good tolerance, a PSA control comparable to conventional fractionation, and the advantage of shorter time period of treatment. This paper reviews the radiobiological findings that have led to the increasing use of hypofractionation in the management of prostate cancer and briefly analyzes the clinical experience in this setting.